The Effect of Planned Behavior and Health Awareness On Intentions of Buying Go Green Ecozisca Products - Fatriani Paloh, Meina; Asnawi, Yudha Heryawan; Taryana, Asep (Indonesian Journal of Business and Entrepreneurship, 2023)
This study aims to analyze the factors that influence consumers buying interest in buying Ecozisca eco-friendly products using the Theory of Planned Behavior approach and health awareness as an intervening factor. The analysis was carried out quantitatively using Structural Equation modeling SmartPLS version 4.0 by purposive sampling. Respondents were taken based on 13 indicators multiplied by 5, totaling 65 respondents. The location used for research is Jakarta because Jakarta is the largest plastic contributor region in Indonesia, although young people already use environmentally friendly products. The results of this study indicate that the intervening factors do not strengthen the influence on consumers buying interest in Go Green Ecozisca products. However, all variables, from attitude variables, subjective norms, and perceptions of behavioral control, influence health awareness and purchase intention of go green products. The strategy that the management of Ecozisca will implement is related to increasing the influence of perceived behavioral control on health awareness because it has the highest influence of 44%. In comparison, 56% is influenced by other factors. In addition, the higher consumer health awareness, the higher the purchase intention to use environmentally friendly products, with an effect of 35%. Although health awareness does not have a powerful influence indirectly, on the other hand, it can influence other factors to become a partial meditator. Ecozisca must focus on business models or strategies that can be implemented to increase the purchase intention of their products, such as using social media campaigns like KOL (Key Opinion Leader) to help convey customers positive information about Ecozisca's eco-friendly products. Keywords: Theory planned behavior, health awareness, buying interest, go green